Noncontiguous finished genome sequences and description of Bacteroides mediterraneensis sp. nov., Bacteroides ihuae sp. nov., Bacteroides togonis sp. nov., Bacteroides ndongoniae sp. nov., Bacteroides ilei sp. nov. and Bacteroides congonensis sp. nov. identified by culturomics. (November 2018) - Andrieu, C.; Mailhe, M.; Ricaboni, D.; Fonkou, M.D.M.; Bilen, M.; Cadoret, F.; Tomei, E.; Armstrong, N.; Vitton, V.; Benezech, A.; Davoust, B.; Levasseur, A.; et al.
Abstract: Culturomics is a concept developing different culture conditions in order to enlarge our knowledge of the human microbiota through the discovery of previously uncultured bacteria. This enabled us to isolate six new species of the Bacteroides genus: Bacteroides mediterraneensis strain Marseille-P2644, Bacteroides ihuae strain Marseille-P2824, Bacteroides togonis strain Marseille-P3166, Bacteroides ndongoniae strain Marseille-P3108, Bacteroides ilei strain Marseille-P3208 and Bacteroides congonensis strain Marseille-P3132. Those bacteria are Gram-negative anaerobic bacilli. We describe here their phenotypic features, together with phylogenetic analysis, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry spectrum, fatty acid composition, and genome sequencing and annotation.